American Economic Journal: Economic Policy - American Economic Association (Pittsburgh, PA American Economic Association, 2010)
American Economic Journal: Economic Policy Publishes papers covering a range of topics, the common theme being the role of economic policy in economic outcomes. Subject areas include public economics; urban and regional economics; public policy aspects of health, education, welfare and political institutions; law and economics; economic regulation; and environmental and natural resource economics.
American Economic Journal: Economic Policy is published quarterly February, May, August and November.
Keywords: Economics; ECONOMICS; ECONOMIC POLICY; PERIODICALS